EVALUASI IMPLEMENTASI KURIKULUM 2013 DI SD PILOTING KABUPATEN KAMPAR - Herman Hidayat; Caska Caska; Dudung Burhanuddin (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2021)
This study aims to evaluate the implementation of the 2013 Curriculum in SD piloting Kampar District. This type of research uses a qualitative descriptive method with an evaluation approach based on curriculum implementation regulations. This evaluation model aims to find out the main tasks and functions of school principals, teachers, education staff and school supervisors in carrying out their duties. 2. The technique of collecting data uses the method of interview, observation and documentation. Data analytical techniques use descriptive analytical models.The results of the study show that from contex evaluation (1) the principal tasks and functions of the principal have been well implemented, but have not been maximized. Likewise the teacher has made the administration of learning well, still needs to be improved in the learning and assessment process. From the input evaluation, the teacher and student manual was not carried out because the books were not available in a timely manner. Teacher and principal training is running well Based on the results of the contex evaluation, the learning process is going pretty well. While the assessment process is going well. The results of the evaluation of the results obtained are that many school residents are happy with the presence of K13 after running in the third year. The results of the study show that there are still obstacles in the implementation, therefore a strategy is recommended to overcome the obstacles to implementing K13 in SD Piloting Kampar District, coordination of the implementation plan, focus on implementation and improve supervision and evaluation